Evaluation of pea genotypes for resistance against powdery mildew caused by Erysiphe pisi - D.K. BANYAL, JAYA CHAUDHARY* and (Indian Phytopathology, 2017)
Powdery mildew of pea caused by Erysiphe pisi DC ex. Saint-Amans is of common recurrence and destructive disease in wet and dry temperate regions of Himachal Pradesh where pea is an important off-season crop. The disease is more prevalent at flowering and pod formation stage and appears in epidemic form almost every year in India and other countries of world. The disease is of utmost importance in Himachal Pradesh as the crop is grown throughout the year in different agro climatic zones of state. Yield losses upto 47 per cent have been reported due to powdery mildew in India by different workers. One of the options for disease control is the use of resistant cultivars. In the present study, 310 germplasm lines of pea (Pisum sativum L.) were screened under net house and artificial epiphytotic conditions under greenhouse. Out of 310 lines, under both i.e. net house and in vitro, a total of 31 lines viz., HFPU, P-1797, P-1783, P-1052, HFP-7, HFP-8, P-1808, P-1820, P-1813, P-1377, P-1422-1, P-1811, IPF-99-25, KMNR-400, LFP-566, LFP-569, LFP-552, LFP-573, JP-501-A/2, PMR-21, KMNR-894, P-1280-4, P-1436-9, P-200-11, IPFD-99-13, HVDP-15, DPP-43-2, LFP-517, LFP-570, JP Ajjila and JP-15 showed highly resistant reaction against powdery mildew.